PENGARUH PERSEPSI SISWA PADA PEMBELAJARAN JARAK JAUH TERHADAP HASIL BELAJAR PAI - Sri Riatni; Abdul Khoir; Irham Irham (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2023)
This study aims to determine the effect of students' perceptions of distance learning onstudents' PAI learning outcomes in terms of knowledge, attitudes and skills at SMA WidyaNusantara. The research method used is a survey method with a correlational approach. The sampleused was 25 students obtained by the Simple Rondom Sampling technique. Collecting data on thevariable X using a questionnaire and the variable Y using the documentation of students' PAIlearning outcomes. The results showed that there was an effect of students' perceptions of distancelearning on students' PAI learning outcomes in terms of knowledge, attitudes, and skills at SMAWidya Nusantara. Aspects of knowledge obtained the value of Sig. 0.000 then the value is 0.000<0.05 or it can be seen that the t count value is 5.096 then 5.096> 2.069 (t table) then it is statedthat H1 is accepted Ho is rejected, and for the relationship of variable X to variable Y on the aspectof knowledge 0.728, by contributing the variance of the X variable to the variable Y on the knowledgeaspect 53%. The attitude aspect is obtained by the value of Sig. 0.000 then the value is 0.000 <0.05or it can be seen that the t count value is 5.656 then 5.656> 2.069 (t table) then it is stated that H1is accepted Ho is rejected, and for the relationship of variable X to variable Y in the attitude aspect0.763, by contributing to the variance of the X variable to the variable Y on the attitude aspect58.2%. Aspects of skills obtained the value of Sig. 0.000 then the value is 0.000 <0.05 or it can beseen that the t count value is 5.403 then 5.403> 2.069 (t table) then it is stated that H1 is acceptedHo is rejected, and for the relationship of variable X to variable Y in the skill aspect 0.748, bycontributing the variance of the X variable to the variable Y on the skill aspect 55.9%.